Valacyclovir as Initial Treatment for Acute Retinal Necrosis: A Pharmacokinetic Modeling and Simulation Study. (3rd July 2017) - Liu, Tao; Jain, Aabha; Fung, Michael; Vinnard, Christopher; Ivaturi, Vijay
ABSTRACT: Purpose : Acute retinal necrosis (ARN) is a feared complication of infectious retinitis most commonly caused by varicella zoster virus (VZV). We performed a pharmacokinetic modeling and simulation study by integrating the existing understanding of physiology with previously published data to evaluate the vitreal penetration of oral valacyclovir for the treatment of ARN, under various dosing scenarios. Method : We compared different oral valacyclovir dosing regimens with intravenous acyclovir. The vitreous compartment was modeled as a peripheral compartment, and paired serum and vitreal acyclovir concentrations were obtained from previously published data of adult patients with ARN undergoing vitrectomy. The efficacy threshold for vitreal acyclovir concentrations was based on the previously reported IC50 values for VZV. Results : Based on the minimum vitreal acyclovir concentrations ( C min ) relative to the mean IC50 for VZV, valacyclovir 1.5 g every 8 hours performed similarly to intravenous acyclovir 700 mg every 8 hours, with the minimum concentration ( C min ) exceeding the mean IC50 after the second dose. In contrast, the standard dosing regimen for herpes zoster, valacyclovir 1 g every 8 hours, performed inferiorly to the intravenous acyclovir regimen throughout the dosing interval. Conclusions : Modeling and simulation data support oral valacyclovir for the treatment of ARN, although the required dosing exceeds the recommended FDA dose size for herpes zoster.